Beyond Borders and States: Modelling Ocean Connectivity According to Indigenous Cosmovisions - Poto, Margherita Paola; Enyew, Endalew Lijalem; Tsiouvalas, Apostolos (Arctic Review on Law and Politics, 2021)
The article describes some common features of Indigenous sea cosmovisions (through examples from Oceania and the Arctic region), from which an understanding of ocean governance rooted in the interconnectedness of all life and the importance of protecting water and people emerges. Hence, the model of ocean (or water) connectivity is characterized by the understanding of ocean-human relationships as a continuum of connections between human and non-human elements. In line with the normative recognition of the sacredness of water, the interconnectedness of all life, and the importance of protecting the sea, Indigenous peoples’ law provides insights and implementation solutions for the restoration of marine ecosystems. This study aims to identify blind spots of the current law-of-the-sea regime, where marine ecological connectivity is not fully recognized as a foundational pillar of effective ocean protection. It also suggests approaches towards knowledge integration mechanisms that could minimize critical issues in ocean governance by enabling the enshrinement of Indigenous nature-oriented approaches within the law of the sea regulatory framework (especially focusing on the high seas’ regime). The work is structured into three main parts: a comprehensive overview of connectivity conceptualizations drawn from Indigenous cosmovisions; reflections on the model’s capability to address law-of-the-sea’s systemic challenges; and concluding reflections on possible future trajectories in law-of-the-sea that could encompass elements of the analyzed model.